Implementasi Metode Total Physical Response (TPR): Strategi Peningkatan Pemahaman Kosakata Bahasa Arab - Aliyah, Muhimmatul; Aliwafa, Aliwafa (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
Arabic is one of the subjects learned in schools. Many students experience difficulties in memorizing and understanding vocabulary due to learning methods that are less engaging. This study aims to describe the implementation of the Total Physical Response (TPR) method in Arabic vocabulary learning at MTsN 3 Surabaya and to determine its effectiveness in improving students’ mastery of mufrodat. This research employed a qualitative method with a descriptive approach. Data were collected through classroom observations and questionnaires. The results indicate that the implementation of TPR created a more active and enjoyable learning atmosphere, enabling students to remember vocabulary more easily through physical movement. Students responded positively to kinesthetic learning activities, and approximately 90% were able to follow the teacher’s instructions correctly. The findings also show an increase in students’ vocabulary comprehension after using TPR. Overall, the TPR method proved effective in enhancing students’ understanding and mastery of Arabic vocabulary.